Paraíso portátil = Portable paradise - Bencastro, Mario (Arte Público Press, 2010)
Salvadoran writer Mario Bencastro examines themes of war, dislocation, and longing in this bilingual collection of stories, poetry, and one novella. Many of his characters are forced to leave their homelands becaus e of violence and poverty. But once in the Promised Land, separated from family and friends and in a country whose language and culture they don't understand, many find themselves overwhelmed by feelings of loss and nostalgia. In "Dragon Boy," a group of children orphaned by El Salvador's civil war band together to survive, even as they are exploited by predators. In "The Plan," a successful Swiss millionaire returns to his native El Salvador--which he left as a defenseless orphan--and executes his ruthless plan to take revenge on those responsible for the brutal killings of his family. And in "From Australia with Love," a Salvadoran emigre plans to marry a countryman she met on the Internet, until they realize that they have met before.